AhmadArdianto,SriZetli ANALISIS BEBAN KERJA MENTAL DAN FISIK PADA OPERATOR FORKLIFT DI PT ABC - Ardianto, Ahmad; Zetli, Sri (Computer Science and Industrial Engineering, 2020)
In general, all human activities are divided into two groups, namely work groups that use mental (brain), and physical (muscle) where both groups really need the work to be done. PT ABC. The First Heritage Dock is a branch of ABC where a company engaged in shipyard. In the department's warehouse there are 3 types of foklift used, namely forklifts with a capacity of 5 tons, 10 tons and 15 tons. Many jobs are given to employees who take mental and physical burdens presented by employees who have work stress. In carrying out the process of analyzing mental burdens for each employee, which is often used in conducting useful research using the NASA-TLX method (Expense Index Duties of National Aeronautics and Space Administration). This method is related to the emergence of the need for subjective reviews consisting of 6 main factors, In carrying out the process of physical work analysis on employees who are often used by research that uses the Cardiovascular Load method while the Cardiovascular Load itself is used to measure heart rate and pulse before doing work and after doing the work thus determines the level felt by an employee. In this study, researchers wanted to calculate the large level of mental work and physical forklift operators. The results of the calculation of mental workload and physical operator of the 5 Ton forklift are 70.38 and 36.36, for 10 Ton are 84.23 and 39.19, and for 15 Ton is 89.17 dam 44.18. It can be concluded that the mental workload of forklifts is very high.